Human cytomegalovirus RNA2.7 inhibits ferroptosis by upregulating ferritin and GSH via promoting ZNF395 degradation. - Mingyi Xu; Shan Ruan; Jingxuan Sun; Jianming Li; Dan Chen; Yanping Ma; Ying Qi; Zhongyang Liu; Qiang Ruan; Yujing Huang (PLoS Pathogens)
Human cytomegalovirus (HCMV) is a herpes virus with a long replication cycle. HCMV encoded long non-coding RNA termed RNA2.7 is the dominant transcript with a length of about 2.5kb, accounting for 25% of total viral transcripts. Studies have shown that HCMV RNA2.7 inhibits apoptosis caused by infection. The effect of RNA2.7 on other forms of cell death is still unclear. In this work, we found that RNA2.7 deletion significantly decreased the viability of HCMV-infected cells, while treatment with ferroptosis inhibitor Fer-1 rescued the infection-induced cell death, demonstrating an anti-ferroptosis role of RNA2.7. The results further showed that RNA2.7 inhibited ferroptosis via enhancing Ferritin Heavy Chain 1 (FTH1) and Solute Carrier Family 7 Member 11 (SLC7A11) expression in Erastin treated cells without involving other viral components. Pooled Genome-wide CRISPR screening revealed zinc finger protein 395 (ZNF395) as a new regulator repressing the expression of FTH1 and SLC7A11. HCMV RNA2.7 promoted proteasome-mediated degradation of ZNF395 that resulted in upregulation of FTH1 and SLC7A11 to inhibit ferroptosis, therefore maintain survival in host cells and complete replication of virus.